2005
DOI: 10.1097/00129492-200503000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Device Nonuse Among Adult Cochlear Implant Recipients

Abstract: The overall prevalence of device nonuse was noted to increase slowly with time. The role of psychologic factors in contributing to the decision of an individual to elect to opt out of device use remains unproven.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 10 publications
1
10
0
Order By: Relevance
“…Most of the interviewed SSD (89.5%) and all AHL (100%) CI recipients wore their CI for six to ten hours daily. The percentage of nonusers was comparable with that for bilateral deaf patients at a rate of 2.8-13% [24,25]. None of the four non-users terminated CI use because of equipment failure or perioperative complications.…”
Section: Wearing Behaviormentioning
confidence: 65%
“…Most of the interviewed SSD (89.5%) and all AHL (100%) CI recipients wore their CI for six to ten hours daily. The percentage of nonusers was comparable with that for bilateral deaf patients at a rate of 2.8-13% [24,25]. None of the four non-users terminated CI use because of equipment failure or perioperative complications.…”
Section: Wearing Behaviormentioning
confidence: 65%
“…Previous studies have reported results only in small cohorts of older adults with limited durations of follow-up. 11-18 The purpose of our study was to investigate long-term rates of CI use in a consecutive case series of older adults (≥60 years) who received their first CI from 1999-2011.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported results only in small cohorts of older adults with limited durations of follow-up. [11][12][13][14][15][16][17][18] The purpose of our study was to investigate long-term rates of CI use in a consecutive case series of older adults (≥60 years) who received their first CI from 1999-2011. …”
mentioning
confidence: 99%